DINÂMICA TEMPORAL DA COBERTURA FLORESTAL NA MICRORREGIÃO CAMPANHA CENTRAL DO RIO GRANDE DO SUL - Vasconcellos, Bruna Nascimento de; Benedetti, Ana Caroline Paim (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2011)
This paper aims to analyze the dynamics of forest cover in Microregion CampanhaCentral. Thematic maps of 2000 and 2010 were developed from Landsat 5 satellite images. Themethodology consisted of the following steps: download and import images, digital processing,pattern recognition and usage coverage and supervised digital classification. From the preparationof maps, one can observe that the forest cover had a total increase of 92,590.99 hectares in themicro. The counties that had been a most significant expansion of the Rosário do Sul was anincrease of 37,685.87 hectares with 34,997.93 hectares São Gabriel. Moreover, in Santa Margaridado Sul was an increase of 11,945.62 hectares and Santana do Livramento of 7,961.57 hectares,which is associated to the abandonment of agricultural areas and the encouragement of forestry.